Science in the Jurisprudence of the US Supreme Court: A Relationship in the Dark (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
This contribution aims to highlight the multiple tensions in the relationship between science and the Supreme Court through an analysis of the jurisprudential strand on the regulation of abortion, in the belief that some of the trends of this paradigmatic jurisprudence can also be extended to other areas of intersection between science and law.
Keywords: US Supreme Court; science; abortion; courts; amicus curiae